Symptoms reported in children of males with type i alcoholism or major depressive disorder: a controlled study - Tufan, Ali Evren; Bilici, Rabia; Topal, Zehra; Demir, Nuran; İzci, Filiz (Journal of Dependence, 2014)
Objective: Parental alcohol use disorders can deleteriously affect children’s health through both genetic and environmental factors. In this study, it was aimed to compare the symptoms reported in children of male patients with Type I alcoholism who applied to the AMATEM department for the first time with those reported by male outpatients being followed with the diagnosis of MDD (First Episode/ Chronic) at the same treatment center and matched healthy controls. Method: This cross-sectional study was conducted at the Elazig Hospital for Mental Disorders. MDD and AMATEM groups were matched in terms of disorder severity measured by CGI. Axis II comorbidity was ruled out by clinical examination. Control group was formed by age-matched males with no psychiatric diagnosis or treatment history. CBCL and CGI-S were used in evaluations and p was set at 0.05. Results: 117 children were enrolled in the study (AMATEM n= 40, MDD n=41, Control n= 36). Control group involved 26, AMATEM and MDD groups involved 20 and 41 fathers; respectively. It was observed that highest scores in CBCL were in the AMATEM group followed by children from MDD and control groups; respectively. The groups differed significantly for all subscales except somatic complaints, anxiety/ depression and total internalizing scores. Discussion: Children of fathers with Type I alcoholism seem to be similar to those of fathers with MDD. Further studies including fathers with Type II alcoholism may help to elucidate the effects of paternal alcoholism on children.